Changing disgust through imagery rescripting and cognitive reappraisal in contamination-based obsessive-compulsive disorder. (March 2018) - Fink, Jakob; Pflugradt, Elisa; Stierle, Christian; Exner, Cornelia
Highlights: Imagery rescripting and cognitive reappraisal were applied to challenge disgust. Participants were OCD patients with washing symptoms and matched controls. In this laboratory study two active strategies were tested against a control condition. Both strategies reduced disgust stronger than a control condition. Both strategies might serve as an additional therapeutic approach to reduce disgust in ERP non-responders. Abstract: Contamination-related obsessive-compulsive disorder (C-OCD) is characterized by strongly experienced disgust and fear, in response to potentially contaminating stimuli. Both emotions differ in their susceptibility for change by habituation and extinction, which are important processes for the success of exposure therapy. Even though the response rates for exposure therapy for C-OCD are very good, it seems promising to test additional therapeutic techniques which target disgust more directly. Therefore, imagery rescripting and cognitive reappraisal were evaluated for their potential to change levels of disgust (within-subject), in the two-session laboratory study with 30 participants, with diagnosed C-OCD, and 30 matched, healthy controls (between-subject), presented. The results show that both emotion-regulation strategies reduced disgust better than a non-intervention control task (counting fishes), across all the participants. Therefore, both strategies seem to be applicable and effective for reducing disgust, in the short term, in participants with diagnosed C-OCD. The implications of these findings for the experimental approach and for the clinical treatment of C-OCD, are discussed.